Enhancing Scientific Communication: Prioritizing User Experience in Audiovisual Interfaces - Mesquita, Cintia Braz [UNESP]; Santos, Adriana Barbosa [UNESP]; de Souza, Rogéria Cristiane Gratão [UNESP] (INSTICC, 2024)
Audiovisual content has emerged as a powerful tool for scientific communication, enabling a broader reach, clearer explanations of complex topics, and greater recognition for researchers. To maximize its impact and fully unleash its potential, accessible and user-friendly interfaces are needed on platforms and mobile apps. This work prioritizes the identification of essential usability requirements for interfaces featuring scientific audiovisual content, aiming to streamline development efforts. Drawing from established literature and an analysis of existing web platforms and mobile apps, we have identified 25 key usability metrics to guide the creation of interfaces that prioritize user experience. Empirical evaluations of these platforms and apps have revealed significant deficiencies in meeting usability criteria such as effectiveness, efficiency, and user satisfaction.
Keywords: Audiovisual; Human-Computer Interaction; Scientific Communication; Usability